Václav Burian’s Non- -obvious Poland - Kulmiński, Robert (Poznańskie Studia Slawistyczne, 2018)
The Polish-studies output of Václav Burian, an ambassador of Polish culture in Czechoslovakia and the Czech Republic, scattered in magazines such as „Ječmínek”, „Hanácké noviny”, „Scriptum”, „Listy” or „Literární noviny”, has been gathered by Jan Jeništa and Anna Militz in a volume entitled Budoucím čtenářům starých novin (For future readers of old newspapers). Their selection of essays from between 1981 and 2014 is an excellent illustration of Václav Burian’s work. The sheer diversity of articles Burian left behind was unquestionably a challenge for the editors. They have stood up to that challenge – it has to be emphasised – outstandingly. They divided the selected texts by subject into three chapters titled: Witness of History (Svědkem Historie), Travel reports (Zprávy z cest) and Literature’s reader (Čtenář literatury). The first covers key events in Poland in the 1980’s. The second consists of Burian’s notes from trips to Poland in 1993 and 1995. The third one collects the most important Burian’s texts about Polish literature. Those three chapters reflect the three areas of Burian’s interest, through which he presented Poland to Czech readers.